2021
DOI: 10.1002/macp.202100378
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bio‐Based Catechol‐Containing Copolymers by Precision Polymerization of Caffeic Acid‐Derived Styrenes Using Ester Protection

Abstract: In this study, ester-protected vinyl catechols (VCs) derived from caffeic acid are synthesized to design novel functional copolymers. The protected VCs are polymerized or copolymerized with a series of common vinyl monomers via reversible addition-fragmentation chain transfer (RAFT) polymerization using cumyl dithiobenzoate as the RAFT agent. The RAFT polymerizations of these protected VCs have been successfully proceeded to afford well-defined polymers with relatively narrow molecular weight distributions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Notably, the disappearance of the peaks at 7.46–7.87 ppm associated with the aromatic protons on the RAFT agent and the color changes (see Figure S2) are indicative of the aminolysis of the RAFT agent when adding the PPG-diamine as the deprotecting agent. The similar aminolysis of RAFT-polymerized P­(Ac 2 VCa) homopolymer using amines was also observed in our previous study, where the corresponding SEC experiment confirmed that the molecular weight will not change significantly after the aminolysis . To deeper understand the function of the PPG-diamine to the PGMA- co -P­(Ac 2 VCa) in this complicated system, the deprotection of the P­(Ac 2 VCa) moiety and the ring opening of the PGMA moiety were further investigated by 1 H NMR spectroscopy under different reaction times (see more details in Supporting Information).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Notably, the disappearance of the peaks at 7.46–7.87 ppm associated with the aromatic protons on the RAFT agent and the color changes (see Figure S2) are indicative of the aminolysis of the RAFT agent when adding the PPG-diamine as the deprotecting agent. The similar aminolysis of RAFT-polymerized P­(Ac 2 VCa) homopolymer using amines was also observed in our previous study, where the corresponding SEC experiment confirmed that the molecular weight will not change significantly after the aminolysis . To deeper understand the function of the PPG-diamine to the PGMA- co -P­(Ac 2 VCa) in this complicated system, the deprotection of the P­(Ac 2 VCa) moiety and the ring opening of the PGMA moiety were further investigated by 1 H NMR spectroscopy under different reaction times (see more details in Supporting Information).…”
Section: Resultssupporting
confidence: 70%
“…The similar aminolysis of RAFT-polymerized P(Ac 2 VCa) homopolymer using amines was also observed in our previous study, where the corresponding SEC experiment confirmed that the molecular weight will not change significantly after the aminolysis. 44 To deeper understand the function of the PPG-diamine to the PGMA-co-P(Ac 2 VCa) in this complicated system, the deprotection of the P(Ac 2 VCa) moiety and the ring opening of the PGMA moiety were further investigated by 1 H NMR spectroscopy under different reaction times (see more details in Supporting Information). The time-dependent 1 H NMR results (Figure S3) focus on the regions for the deprotection of the P(Ac 2 VCa) moiety (H g , H g′ and H g″ :6.0−7.1 ppm) and the ring opening of the PGMA moiety (H d :2.6−2.9 ppm), and the results indicated that the PPG-diamine favors to deprotect the P(Ac 2 VCa) moiety than to ring-open the PGMA moiety in the solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the radical scavenging ability of catechol during RAFT remains a problem, and so most examples in the literature make use of protecting groups to temporarily shield the catechol unit during polymerization. For instance, methoxy, acetonide, silyl, and ester protecting groups have all been used in the synthesis of catechol polymers by RAFT. A drawback of this approach is that the deprotection step often requires harsh reagents such as BBr 3 , HBr, or TFA, which can inadvertently affect other groups within the polymer (e.g., comonomers or the active chain ends) and cause partial oxidation of the catechols .…”
Section: Introductionmentioning
confidence: 99%
“…These new biobased latexes, obtained by a RAFT-mediated aqueous emulsion PISA process, pave the way for the formation of a new class of biobased paints, coatings or adhesives. In addition, deprotection of acetoxy groups 17 can lead to phenolic functions in polymers, which may be interesting for future applications.…”
Section: Discussionmentioning
confidence: 99%
“…Among aldehyde residues, the most well-known example is the versatile molecular vanillin platform [11][12][13][14] , which allows the formation of biobased polymers and networks through various chemical modifications. Other alternatives derived from cinnamic acid, ferulic acid, sinapic acid and caffeic acid have also been developed, allowing access to radically polymerizable monomers containing catechyl (C) [15][16][17] , guaiacyl (G) [18][19][20][21][22][23][24][25][26][27] , syringyl (S) 21,22,[28][29][30] and hydroxyphenyl (H) 21,22,31,32 units and their biobased polymer counterparts.…”
Section: Introductionmentioning
confidence: 99%